Thoracic Gunshot Wound with Vascular Lesion - Ahmad Adityawarman; Ahmad Ghozali (Fakultas Kedokteran Universitas Lambung Mangkurat, 2021)
Abstract: The thoracic gunshot wounds may cause high morbidity and mortality, especially if accompanied by vascular injuries. Therefore, immediate management and precise decision are needed. A 35-year-old man who was referred from the regional hospital presented with thoracic gunshot wound and a history of hemorrhagic shock. A projectile was found through the chest wall and caused axillary artery rupture. The patient underwent exploratory thoracotomy and axillo-brachial artery bypass using a great saphenous vein graft. The patient's postoperative condition showed improvement in hemodynamic and distal limb perfusion. Keywords: Chest trauma, gunshot wound, axillary artery, vascular injury